A Study Comparing Modified Alvarado Score and Tzanakis Score For Diagnosing Acute Appendicitis - Yadav, Hankey; Agrawal, Praveen; Hussain, Shaik; Dhananjay, Talaviya (Journal of Neonatal Surgery, 2025)
Background & Methods: The aim of the study is to compare the accuracy of the Modified Alvarado Score and Tzanakis Score in Diagnosing Acute Appendicitis. Informed written consent was obtained from all patients. This prospective, non-randomized study included patients admitted to the Department of General Surgery at KD Medical College, Mathura, over two years, with clinical suspicion of acute appendicitis who underwent appendicectomy. Results: 60 had a Tzanakis score of more than 8, with 56 having a Modified Alvarado score of more than 7. The remaining 18 cases had a Tzanakis score of less than 8, with 15 having a Modified Alvarado score of less than 7 Conclusion: The study demonstrates that both the MAS and the Tzanakis Score are reliable and effective tools for the preoperative diagnosis of acute appendicitis. However, the Tzanakis Score offers superior sensitivity and specificity, particularly in cases where the diagnosis is uncertain. Its higher accuracy, as evidenced by its correlation with histopathological confirmation, suggests that it may be a preferred diagnostic tool in clinical settings. While the MAS remains a useful tool, the Tzanakis Score's broader scoring range allows for finer diagnostic stratification, potentially reducing unnecessary appendectomies and improving patient outcomes